PERANCANGAN BUKLET PROFIL SMP ISLAM TERPADU DARUL HIKMAH PASAMAN BARAT - Maretha Ramadhani, Drs. muzni Ramanto, Eliya Pebriyeni, S.Pd, M. Sn (Serupa The Journal of Art Education, 2013)
The purpose of this promotion booklet design was (1) to promote SMP Islam Terpadu Darul Hikmah Pasaman Barat toward the society of Pasaman Barat and out of Pasaman Barat, (2) to design an effective, efficient, and interesting bucklet visually and verbally, so that the aim and the purpose of this design could be achieved, (3) to create a spesific design. The data was collected by using primery and secondary sources. The methodology of research used in creating this final project was analysis of 5W+1H (What, Who, Why, When, Where, How). The result of this design was the profil booklet of SMP IT Darul Hikmah Pasaman Barat. Kata Kunci: perancangan, buklet, profil.